SGI-4 in Monophasic Salmonella Typhimurium ST34 Is a Novel ICE That Enhances Resistance to Copper - Branchu, Priscilla; Charity, Oliver J.; Bawn, Matt; Thilliez, Gaetan; Dallman, Timothy J.; Petrovska, Liljana; Kingsley, Robert A. (Frontiers in Microbiology, 2019)
A multi drug resistant Salmonella enterica 4,[5],12:i- of sequence type 34 (monophasic S. Typhimurium ST34) is a current pandemic clone associated with livestock, particularly pigs, and numerous outbreaks in the human population. A large genomic island, termed SGI-4, is present in the monophasic Typhimurium ST34 clade and absent from other S. Typhimurium strains. SGI-4 consists of 87 open reading frames including sil and pco genes previously implicated in resistance to copper (Cu) and silver, and multiple genes predicted to be involved in mobilization and transfer by conjugation. SGI-4 was excised from the chromosome, circularized, and transferred to recipient strains of S. Typhimurium at a frequency influenced by stress induced by mitomycin C, and oxygen tension. The presence of SGI-4 was associated with increased resistance to Cu, particularly but not exclusively under anaerobic conditions. The presence of silCBA genes, predicted to encode an RND family efflux pump that transports Cu from the periplasm to the external milieu, was sufficient to impart the observed enhanced resistance to Cu, above that commonly associated with S. Typhimurium isolates. The presence of these genes resulted in the absence of Cu-dependent induction of pco genes encoding multiple proteins linked to Cu resistance, also present on SGI-4, suggesting that the system effectively limits the Cu availability in the periplasm, but did not affect SodCI-dependent macrophage survival.